Quality of information transferred to palliative care - Kuusisto Anne; Saranto Kaija; Korhonen Päivi; Haavisto Elina (WILEY, 2025)
Aims and objectives: To describe the quality of information coming from previous care units to palliative care.
Background: Information quality is an interconnected concept that includes different dimensions and can be viewed from different perspectives. More knowledge is needed from a multi-professional perspective on the information quality coming to palliative care.
Design: Descriptive qualitative study.
Methods: Altogether 33 registered nurses, practical nurses, social workers and physicians working in palliative care were purposively selected to participate in thematic interviews. The research was carried out in six palliative care units in three hospital districts. The data were analysed by using deductive and inductive content analysis. The COREQ checklist was used.
Results: Three main categories with thirteen categories were identified in connection with the deductive analysis based on the Clinical Information Quality framework: (1). Informativeness of information coming from previous care units to palliative care included accuracy, completeness, interpretability, plausibility, provenance and relevance. (2). Availability of information coming from previous care units to palliative care included accessibility, portability, security and timeliness. (3). Usability of information coming from previous care units to palliative care included conformance, consistency and maintainability. Each category is divided into sub-categories followed by narratives of their content.
Conclusions: This study provides new knowledge on the quality of information coming to palliative care from a multi-professional perspective. Professionals working in palliative care units highlight issues describing good information quality, but also point out quality issues and areas for improvement.
Relevance to clinical practice: The results can guide the development of documentation practices and Health Information System development as well as be used in the generation of a new audit instrument of information quality.